Expression of the oxygen-sensitive transcription factor subunit HIF-1α in patients suffering from secondary Raynaud syndrome - Heger Lukas Andreas; Kerber Mark; Hortmann Marcus; Robinson Samuel; Mauler Maximilian; Stallmann Daniela; Duerschmied Daniel; Bode Christoph; Hehrlein Christoph; Ahrens Ingo (Acta Pharmacologica Sinica, 2019)
Anti-ischemic therapy remains a challenge due to the complexity of hypoxia response pathways. Hypoxia-inducible factor (HIF)-1 is a heterodimer transcription factor consisting of 2 subunits, HIF-1α and HIF-1β. Hypoxia-dependent activation of HIF-1α regulates cellular O2 homeostasis. Raynaud syndrome (RS), as a comorbidity of the autoimmune disease systemic sclerosis (SS), is characterized by vasospasms that limit blood ﬂow to the limbs, resulting in hypoxia. A single-center randomized study was conducted to compare prostaglandin E1 (PgE1) therapy with a treatment combining PgE1 and an endothelin-1 blocker, bosentan. A total of 30 patients suffering from SS with RS were enrolled. We examined the regulation of HIF-1α, its target heme oxygenase-1 (HMOX-1), and the serum levels of the HIF-1α protein in a subset of patients as well as in ten healthy individuals. The expression of HIF-1α and HMOX-1 in monocytes was measured using absolute plasmid-based quantitative real-time PCR, whereas serum HIF-1α levels were measured with ELISA. Samples were taken at the time of randomization and after 24 weeks. We found that HIF-1α and HMOX-1 mRNA expression in monocytes and serum HIF-1α protein levels were signiﬁcantly higher in the SS/RS patients compared to the healthy control group. Single-drug therapy signiﬁcantly increased HIF-1α and HMOX-1 mRNA expression in monocytes and serum HIF-1α protein levels in the SS/RS patients compared to those at the time of randomization, whereas combining PgE1 with an endothelin-1 blocker prevented the further increases in HIF-1α and HMOX-1 expression. We propose HIF-1α and HMOX-1 as novel markers for anti-ischemic therapy in RS.